PENGEMBANGAN GAYA MENGAJAR DAN TEKNIK PERTOLONGAN DI LAUT BAGI ANAK-ANAK SEKOLAH DASAR - - Asim (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2009)
The purposes of this research were to develop a teaching style and a rescue technique in the sea’ accident. The design of the research was research and design (R&D). The subjects were 15 physic education’ and 45 elementary schols’ students (grade 4,5,6) from Prigi coast area. The data data collection intruments were questionaire and observation. The collected data were analysed by descriptive analysis technique. The research products were a teaching style and a rescue technique in the sea’ accident.